Penataan Fasilitas Parkir Dan Fasilitas Umum Berbasis Masyarakat (Pengempon Pura) di Pura Sad Kahyangan Luhur Andakasa - Rai Asmani K Anak Agung; I Wayan Jawat; Cri Vinantya Laksmi Ida Ayu (Fakultas Teknik Universitas Warmadewa, 2023)
Pura Sad Kahyangan Luhur Andakasa is one of the temples that is a prayer destination for Hindus in Bali. This temple is located in Gegelang Village, Manggis District, Karangasem Regency. This temple is one of the temples visited by many pilgrims. The high level of public interest in praying at Puru Luhur Andakasa needs to be supported by adequate parking for the vehicles used by pilgrims. Apart from that, the existing parking area is also used by traders to sell. Therefore, based on requests from community leaders and the administrators of Pura Luhur Andakasa, the dedication was focused on macro and micro issues raised by local community leaders regarding the arrangement of land for parking plots and kiosks for traders selling around the Pura Luhur Andakasa area. In carrying out this service, a measurement method is used, which will then be expressed as a design for parking lots and selling blocks/kiosks for traders.